Microirrigation for Home Landscapes - Anne E. Yasalonis; Michael D. Dukes (EDIS)
Microirrigation is a way to water plants using low-pressure and low flowrates (usually 15 psi or less and 60 gph or less).  It can be easy to install and inexpensive to purchase.  Install microirrigation above, on, or below the soil or mulch in landscape beds.  There are four types of microirrigation systems available.